Design of a Medical Clinic at Kabale University, Faculty of Engineering Technology, Applied Design and Fine Art. - Mugarura, Peter (Kabale University, 2023)
This report is about the Design of a Medical Facility at the Engineering Faculty Kabale University Nyabikoni. It has three chapters; Chapter one: Introduction of the project, the problem statement as well as the objectives of the project. Chapter two: Methodology, data collection techniques and parameters, drawings and benchmarked areas. Chapter three: Correlated discussion about the project, conclusions and recommendations.